Optimisation of sugar and solid biofuel co-production from almond tree prunings by acid pretreatment and enzymatic hydrolysis - Manuel Cuevas-Aranda; Mª Lourdes Martínez-Cartas; Fahd Mnasser; Adnan Asad Karim; Sebastián Sánchez (Bioresources and Bioprocessing, 2024)
Abstract Almond pruning biomass is an important agricultural residue that has been scarcely studied for the co-production of sugars and solid biofuels. In this work, the production of monosaccharides from almond prunings was optimised by a two-step process scheme: pretreatment with dilute sulphuric acid (0.025 M, at 185.9–214.1 ℃ for 0.8–9.2 min) followed by enzyme saccharification of the pretreated cellulose. The application of a response surface methodology enabled the mathematical modelling of the process, establishing pretreatment conditions to maximise both the amount of sugar in the acid prehydrolysate (23.4 kg/100 kg raw material, at 195.7 ℃ for 3.5 min) and the enzymatic digestibility of the pretreated cellulose (45.4%, at 210.0 ℃ for 8.0 min). The highest overall sugar yield (36.8 kg/100 kg raw material, equivalent to 64.3% of all sugars in the feedstock) was obtained with a pretreatment carried out at 197.0 ℃ for 4.0 min. Under these conditions, moreover, the final solids showed better properties for thermochemical utilisation (22.0 MJ/kg heating value, 0.87% ash content, and 72.1 mg/g moisture adsorption capacity) compared to those of the original prunings. Graphical Abstract